(untitled) (International Journal of Engineering and Computer Science, 2017)
In this paper we propose an intelligent parking system which aims to avoid wastage of time and fuel to find an empty spot in a parking lot. Many of the existing systems only provide details about the number of empty spots in the parking area, which is insufficient as the user still has to find the parking spot to park his vehicle the parking lot. Our system not only indicates the number of empty spots but also guides the driver to the nearest parking spot to him/her through an android based application. The system also comprises of a booking feature through which the user can book his parking spot beforehand